2020
DOI: 10.4081/ejtm.2020.8722
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of high novelty-seeking on academic burnout: Moderating effect of physical activity

Abstract: A large number of studies have shown a positive correlation between high novelty-seeking (HNS), substance/medication use (S/MU), high physical activity (HPA), and academic burnout (AB); however, the outcome of individuals with HNS in the terms of catching AB is doubtful. The present study was conducted to find out whether the personality traits such as HNS in medical students predisposes the AB or decreases its severity by increased physical activity (PA). This cross-sectional study, 227 medical students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The model of employee burnout was first developed by Maslach based on Freudenberger’s view, which consisted of three dimensions, namely, exhaustion, depersonalization, and reduced personal accomplishment. 14 According to the World Health Organization (WHO) definition, 15 occupational burnout is a clinical condition resulting from chronic work-related stress, with symptoms marked by “feelings of energy depletion or exhaustion; increased mental distance from one’s job, or feelings of negativism or cynicism related to one’s job; and reduced professional efficacy.” During the recent outbreak of COVID-19, hospitals have been forced to rapidly provide clinical facilities and healthcare teams to quell the rising tide of COVID-19 patients. To meet the growing demand of COVID-19 patients, healthcare systems worldwide have been forced to send many healthcare workers to areas outside their usual clinical specialty and/or expertise, often with extra shifts and long working hours.…”
Section: Resultsmentioning
confidence: 99%
“…The model of employee burnout was first developed by Maslach based on Freudenberger’s view, which consisted of three dimensions, namely, exhaustion, depersonalization, and reduced personal accomplishment. 14 According to the World Health Organization (WHO) definition, 15 occupational burnout is a clinical condition resulting from chronic work-related stress, with symptoms marked by “feelings of energy depletion or exhaustion; increased mental distance from one’s job, or feelings of negativism or cynicism related to one’s job; and reduced professional efficacy.” During the recent outbreak of COVID-19, hospitals have been forced to rapidly provide clinical facilities and healthcare teams to quell the rising tide of COVID-19 patients. To meet the growing demand of COVID-19 patients, healthcare systems worldwide have been forced to send many healthcare workers to areas outside their usual clinical specialty and/or expertise, often with extra shifts and long working hours.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that these network features of individuals may not be replicated in the similar way. Fourth, other confounding factors, such as demographic characteristics (e.g., working years and working hours), personality, resilience, and empathy (66)(67)(68)(69), may also influence the relation between MW and burnout. Therefore, future research could further explore the MW-burnout network under the control of these confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions such as implementing cognitive behavioral therapy (CBT) and mental health education courses in medical education have already been demonstrated to be effective in helping medical students reduce maladaptive perfectionism levels, decrease academic burnout levels and increase life satisfaction levels (Chand et al, 2018;Wang and Du, 2020). In addition, two recent cross-sectional studies by Khosravi and Khosravi et al found that academic burnout was significantly associated with physical activities in medical students and encouraging medical students to do more physical exercise may lower their academic burnout levels (Khosravi et al, 2020;Khosravi, 2021). In this regard, interventional studies need to be conducted in the future to examine the effectiveness of physical activities in helping medical students reduce academic burnout.…”
Section: Implications and Limitationsmentioning
confidence: 99%